Neither free trade nor protection : a critical political economy of trade theory and practice - Dunn, Bill (Cheltenham Edward Elgar Publishing Ltd., 2015)
Neither Free Trade Nor Protection provides a critical exploration of mainstream and alternative theories of international trade and presents original evidence of trade's consequences. It rejects the choice between openness and closure. Mainstream economists almost always support 'free trade' but their arguments for this are flawed and too often rely on a caricature of their opponents as simple-minded protectionists. Meanwhile, many critics successfully emphasize shortcomings of the orthodoxy but struggle to identify a more positive agenda, either seeing free trade as a desirable, if unachievable, end or equally simplistically blaming trade for international (From Amazon page)
1. Introduction: Contesting the conservative antinomies of trade theory -- 2. The making of World trade -- 3. Free trade theory and its critics -- 4. Market imperfections and state strategies -- 5. Marxism, trade and the limits of radical nationalism -- 6. Evaluating trade and growth -- 7. Factor endowments, trade and growth -- 8. International trade and inequality within countries -- 9. Trade opening and the decline of industrial action -- 10. Global restructuring, trade and the crisis of 2007-09 -- 11. Conclusions&nbsp
Includes bibliographical references (pages 203-222) and index.
Keywords: International Trade; INTERNATIONAL TRADE; INTERNATIONAL ECONOMIC RELATIONS; PHILOSOPHY; THEORY